2022
DOI: 10.3390/ijerph19138117
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Assessment in Students from Polish Universities during the COVID-19 Pandemic According to WHO Quality of Life Questionnaire

Abstract: The outbreak of COVID-19 in December 2019 in China influenced the lives of people all over the world. Many had to face the completely new situation of lockdown. These changes influenced many aspects of life. Students’ quality of life changed as well. The aim of the study was to assess the differences in the quality of life of students with regard to the field of study and the knowledge regarding medicine. The study population consisted of 500 students from three Polish universities (Medical University of Siles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…However, since the beginning of the COVID-19 pandemic, university students had to also deal with further changes which abruptly occurred in their life [ 8 , 9 ], potentially eliciting notable levels of stress related to the control measures (i.e., isolation due to the lockdown) and to the fear of being infected and infecting others, as well as to the drastic modifications in the relational and social life [ 10 , 11 , 12 ]. From this perspective, the COVID-19-related changes have deeply affected students’ interpersonal life, entailing specific experiences (i.e., loneliness; lack of connection; a frustrated sense of belonging) which expose them to a significantly high risk for psychological health [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, since the beginning of the COVID-19 pandemic, university students had to also deal with further changes which abruptly occurred in their life [ 8 , 9 ], potentially eliciting notable levels of stress related to the control measures (i.e., isolation due to the lockdown) and to the fear of being infected and infecting others, as well as to the drastic modifications in the relational and social life [ 10 , 11 , 12 ]. From this perspective, the COVID-19-related changes have deeply affected students’ interpersonal life, entailing specific experiences (i.e., loneliness; lack of connection; a frustrated sense of belonging) which expose them to a significantly high risk for psychological health [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted so far clearly confirm that the COVID-19 pandemic has significantly influenced various aspects of Health-Related Quality of Life (HRQoL) [16,17]. Furthermore, as noted in an observation conducted in early 2020 by Wang et al [18], in order to better understand the levels of psychological impact, anxiety, depression, and stress during the initial stage of the COVID-19 outbreak, female gender, student status, and poor self-rated health status were significantly associated with a greater psychological impact of the outbreak and higher levels of stress, anxiety, and depression (p < 0.05). Therefore, in our study, in order to assess health-related quality of life in females, we opted to use the 15D instrument, which is a general, comprehensive (15-dimensional), and standardized instrument for measuring health-related quality of life in individuals over 16 years of age.…”
Section: Introductionmentioning
confidence: 69%
“…Second, the uneven distribution of sex in our sample, due to the overrepresentation of women in psychology programs, could potentially impact the generalizability of the findings. Specifically, research by Trzcionka et al revealed differing responses to stressful situations among male and female students, with women in technical fields exhibiting lower resistance and those in medical sciences displaying higher levels of resilience [58]. Third, the sample size was relatively small, potentially limiting the statistical power of the analysis.…”
Section: Discussionmentioning
confidence: 99%